(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Within this paper we focus on the representation of open educational resources based on the agent-based modeling. The open educational resources (OER) concept is introduced as well as the agent-based modeling approach (ABM). We then propose to represent an OER by an agent and to take into account some properties such as its dynamic aspect and its behaviors. An agent structure in then introduced based on the modeling of learning objects.